Risks of a lifetime in construction Part I: Traumatic injuries. Issue 9 (24th July 2014) - Dong, Xiuwen Sue; Ringen, Knut; Welch, Laura; Dement, John
<x xml:space="preserve">Abstract</x> Background Estimates of occupational risk are typically computed on an annual basis. In contrast, this article provides estimates of lifetime risks for fatal and nonfatal injuries among construction workers. A companion paper presents lifetime risks for occupational illnesses. Methods Using 2003–2007 data from three large data sources, lifetime risk was computed based on the number of fatal and nonfatal injuries per 100 FTEs for a working lifespan of 45 years. Results For a working life in construction, the risk of fatal injuries were approximately one death per 200 FTE, and the leading causes were falls and transportation incidents. For nonfatal injuries resulting in days away from work, the adjusted lifetime risk was approximately 78 per 100 FTEs, and the leading causes were contact with objects/equipment, overexertion, and falls to a lower level. Conclusions Lifetime risk estimates help inform both workers and policymakers. Despite improvements over the past decades, risks in construction remain high. Am. J. Ind. Med. 57:973–983, 2014. © 2014 Wiley Periodicals, Inc.